Correction: Enhanced anti-Stokes luminescence in LaNbO4:Ln3+ (Ln3+ = Yb3+, Er3+/Ho3+/Tm3+) with abundant color. Issue 31 (31st March 2017) - Huang, Huining; Zhou, Haifeng; Zhou, Juan; Wang, Tao; Huang, Dapeng; Wu, Yaqiang; Sun, Leilei; Zhou, Guangjun; Zhan, Jie; Hu, Jifan
Abstract : Correction for 'Enhanced anti-stocks luminescence in LaNbO4 :Ln 3+ (Ln 3+ = Yb 3+, Er 3+ /Ho 3+ /Tm 3+ ) with abundant color' by Huining Huang et al., RSC Adv., 2017, 7, 16777–16786.